1999
DOI: 10.1161/01.atv.19.4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Poor Glycemic Control Predicts Coronary Heart Disease Events in Patients With Type 1 Diabetes Without Nephropathy

Abstract: Abstract-Patients with type 1 diabetes mellitus, especially those with nephropathy, are at increased risk for coronary heart disease (CHD). However, information on the predictive value of cardiovascular risk factors and the degree of hyperglycemia with respect to CHD events in patients with type 1 diabetes without nephropathy is still incomplete. Therefore, we performed a prospective study on risk factors for CHD in patients with type 1 diabetes free of clinical nephropathy. At baseline examination, cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 39 publications
5
59
1
8
Order By: Relevance
“…This assertion, based on the observation that the only strong epidemiological glycaemia-CAD link was in the Lehto et al study [6] of participants without renal disease, is also consistent with the DCCT/EDIC trial data. In DCCT/EDIC, a reduction in the risk of CVD events in the intensive insulin therapy group was reported, where both a fall in HbA 1c occurred and renal disease was less apparent [13].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This assertion, based on the observation that the only strong epidemiological glycaemia-CAD link was in the Lehto et al study [6] of participants without renal disease, is also consistent with the DCCT/EDIC trial data. In DCCT/EDIC, a reduction in the risk of CVD events in the intensive insulin therapy group was reported, where both a fall in HbA 1c occurred and renal disease was less apparent [13].…”
Section: Discussionsupporting
confidence: 72%
“…One study stratified variables by sex [6]; therefore, values were recalculated to pool results for men and women. The CAD outcome in each study was myocardial infarction or death due to CAD.…”
Section: Comparative Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic hyperglycaemia might also increase the risk for coronary artery disease by many mechanisms, such as abnormalities in lipoprotein particle composition, irreversible glycation of proteins in the arterial wall [54], acceleration of thrombus formation [54] and oxidation of lipoproteins [55] or worsening of insulin resistance and hyperinsulinaemia [56]. Consistent with that many [20,21,22,23] but not all studies [57,58] have found that higher HbA 1c is a predictor for macrovascular complications. We found that HbA 1c was inversely associated with hyperaemic adenosine stimulated myocardial blood flow in the pooled data but not in the diabetic or non-diabetic subjects alone.…”
Section: Discussionmentioning
confidence: 70%
“…Poor glycaemic control seems to act as an independent risk factor for coronary artery disease in diabetic patients [20,21,22,23]. Chronic hyperglycaemia in Type I diabetes is associated with impaired endothelium-dependent vasodilation [24,25] which might be due to reduced availability of nitric oxide during hyperglycaemia [26].…”
mentioning
confidence: 99%